INFLUENCE OF SERVICE QUALITY, PRICE AND LOCATION ON CUSTOMER SATISFACTION AT AHASS 05468 WORKSHOP SETYA MOTOR SURABAYA (HONDA DEAD C ) - Kunto Inggit Gunawan; Ec. Mataji (Sean Institute, 2023)
This research is a study conducted at the AHASS 05468 Setya Motor Surabaya workshop with the title